Atypical Presentation of Skull Metastasis from Rectal Adenocarcinoma as an Initial Symptom of Recurrence - Cemal Fırat; Ahmet Hamdi Aytekin; Serkan Erbatur; Nasuhi Engin Aydın; Engin Burak Selcuk (Case Reports in Medicine)
Most malignant rectal tumors are histopathologically characterized as adenocarcinoma and generally metastasize to distant organs such as the lungs or the liver. Metastasis of rectal carcinomas to the skull is extremely rare. This study reports the initial diagnosis of rectal adenocarcinoma recurrence in a 65-year-old female with scalp metastasis. The patient’s history indicated a colorectal adenocarcinoma that was resected five years earlier. A skull metastasis from a rectal adenocarcinoma has not yet been reported in the literature as an initial symptom for recurrence. This paper suggests that skull metastasis from any part of the body must be considered in the differential diagnosis of soft tissue tumors in the skull even in the absence of intestinal symptoms.